EFEKTIVITAS KEGIATAN EKSTRAKURIKULER IKATAN REMAJA MASJID (IRMA) DALAM MENUMBUHKAN SIKAP TOLERANSI BERAGAMA SISWA - Miftahul Huda; Imas Kurniasih; Muhtadin; Mukhlishah; Fitrah Alawiah (Fakultas Agama Islam, Universitas Mathla'ul Anwar, 2024)
In this modern era, religious tolerance is very necessary to create a harmonious and peaceful nation amidst the religious diversity of Indonesian society. IRMA extracurricular is an Islamic spiritual organization in schools which is expected to be an effective means of instilling attitudes of religious tolerance in students. IRMA's extracurricular activities support religious extracurricular activities by providing education, coaching and developing the potential of Muslim students to become people of faith, devoted to Allah SWT. and have noble character. This research aims to determine the effectiveness of extracurricular activities of the Mosque Youth Association (IRMA) on students' religious tolerance attitudes. The research method used is a descriptive analysis method, and the research approach used is a qualitative approach. The results of the research show that the effectiveness of IRMA extracurricular activities has a quite good impact in fostering students' religious tolerance, this is shown by the attitudes: 1) Recognizing everyone's rights, 2) Respecting other people's beliefs, 3) Agreeing in dissent, 4) Understanding each other